2022
DOI: 10.21608/ejhm.2022.266025
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Manual Coordination, Strength and Hand Pain in Normal Teenage Students: A Cross-Sectional Study

Abstract: Background: These days, we can't imagine living without our smartphones. Physical functions of your hands and fingers like dexterity and coordination could be impaired from too much time spent on your smartphone due to the constant grasping and tapping of its screen. Objective: The purpose of this study was to look into how smartphone addiction affects normal adolescent students' manual coordination (manual dexterity and upper limb coordination), grip strength, pinch strength, and wrist and hand pain. Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[ 1 ] Recent evidence has reported the correlation between smartphone addiction and neck muscle endurance. [ 37 ] Numerous research studies have documented a decrease in muscle strength and endurance as a consequence of muscle imbalance and motor control issues in patients with mechanical neck pain. [ 29 ] In a study that set out to determine the endurance of cervical flexor muscles, Agrawal and Hande found that chin tuck-in exercises aid in strengthening deep cervical flexors, while active cervical exercises enhance the endurance of cervical flexor muscles in individuals with prolonged smartphone users.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Recent evidence has reported the correlation between smartphone addiction and neck muscle endurance. [ 37 ] Numerous research studies have documented a decrease in muscle strength and endurance as a consequence of muscle imbalance and motor control issues in patients with mechanical neck pain. [ 29 ] In a study that set out to determine the endurance of cervical flexor muscles, Agrawal and Hande found that chin tuck-in exercises aid in strengthening deep cervical flexors, while active cervical exercises enhance the endurance of cervical flexor muscles in individuals with prolonged smartphone users.…”
Section: Discussionmentioning
confidence: 99%